2022
DOI: 10.1155/2022/3169834
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Misophonia with Risperidone in a Patient with Autism Spectrum Disorder

Abstract: We report the case of a 32-year-old male with autism spectrum disorder (ASD) suffering from severe misophonia. After titrating risperidone to 2 mg twice a day, the patient reported a significant reduction in his symptoms and his Amsterdam misophonia scale-revised (AMISOS-R) score dropped by from 31 to 5. Upon discharge, the patient was noted to have decreased irritability and overall improved behavior and effect. This significant symptomatic improvement was likely not explained by inpatient admission alone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While the A-Miso-S score was 15 when the patient did not take propranolol, the A-Miso-S score was recorded as 2 when the patient took propranolol (Webb 2022). Pan et al (2022) reported a 32-year-old male patient with autism spectrum disorder and severe misophonia who experienced behavioral outbursts in response to trigger sounds. It was noted that the patient, who was given 2 mg risperidone twice a day, felt less irritable and could tolerate trigger sounds, and his A-Miso-S score decreased from 31 to 5 (Pan et al 2022).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…While the A-Miso-S score was 15 when the patient did not take propranolol, the A-Miso-S score was recorded as 2 when the patient took propranolol (Webb 2022). Pan et al (2022) reported a 32-year-old male patient with autism spectrum disorder and severe misophonia who experienced behavioral outbursts in response to trigger sounds. It was noted that the patient, who was given 2 mg risperidone twice a day, felt less irritable and could tolerate trigger sounds, and his A-Miso-S score decreased from 31 to 5 (Pan et al 2022).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Thus far, no randomized trials have assessed the effects of any medication on misophonia or misokinesia symptoms. Published reports suggest that antidepressants [ 6 , 7 ], beta-blockers such as propranolol [ 8 ], and mood-stabilizing antipsychotics such as risperidone [ 9 , 10 ] may alleviate symptoms in some cases. Potent psychotomimetic drugs, such as psilocybin, ketamine, and MDMA, hold theoretical potential for addressing some of the core symptoms of misophonia and misokinesia, although this is still a hypothesis that will require clinical assessment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%